Buying and selling how trading shapes our world - Schrank, Jeffrey; Learning Seed Company (Chicago, Ill. : Learning Seed, 2008)
Presents an overview of the central concepts of commerce. Learn why the global marketplace of buying and selling is far more than a convenient way to get the stuff we crave-it shapes personal freedom and drives material progress
DVD Format
With English subtitle
Keywords: Marketing; Selling; Economics; Consumer education; Commerce; Exchange